Effect of educational technology on students’ foreign language anxiety: a thematic literature review - Mingyan, Ma; Noordin, Nooreen; Razali, Abu Bakar (Sciedu Press, 2022)
Foreign language anxiety (FLA), as a common affective filter, has impeded the language learning process. In order to reduce the FLA, researchers have explored several methods via enhancing language learning settings. Technology as a crucial tool in improving the learning environment has been considered on this topic as well. However, the results of these empirical studies are inconsistent. After reviewing 24 relevant experimental and quasi-experimental research articles from 2016 to 2021 and calculating the effect size for each article, it is evident that 46% of studies reported that technology-assisted instruction significantly decreased FLA, and 54% had no significant effect on FLA. Therefore, this paper aimed to examine the overall effect size on the topic and explore the moderators that caused these inconsistent results through examining five potential moderators (technology type, using methods for integrating technology into a foreign language classroom, exposure duration of technology in experimental groups, FLA type and target language) from the reviewed studies, which are based on the sources of FLA (Young, 1991; Yan & Horwitz, 2008). Two moderators (using methods for integrating technology into foreign language classrooms and target language) were found to get significant predictions on the effect of technology on students' FLA, p<0.05. These findings provide educators, researchers, and practitioners a new direction for future research on different methods of teaching the target language using suitable technology in the classroom.